Production of bacterial cellulose effect of different mediums and modes of operation - Muhammad Syafiq, Khirrudin (2012)
Bacterial cellulose,an exopolysaccharide produced by Acetobacter Xylinum s.p,has unique structural and mechanical properties and is highly pure as compared to plant cellulose.This objective of this study was to assess the effect of different medium (Hestrin Schramm medium, banana peel,coconut water,and hibiscus waste) on microbial decomposition using three categories of operation mode (Batch, fed-batch and repeated batch).Production of bacterial cellulose in this experiment include the production of inoculum using the fresh coconut water and it was conduct under optimum temperature and pH which is 30oC and 5.5 respectively.From the result,banana peel gives the highest yield in fed batch mode of operation,followed by coconut water,hibiscus waste and Hestrin Schramm medium. The high production efficiency of banana peel was due to the high purity of carbon source in banana peel and the continuously feeding of the fermentation medium using the fed batch mode.These results show that,the consumption of carbon source is not the only factor that effects the efficiency production of bacterial cellulose.The operation mode might play another important factor in the production of bacterial cellulose.From the FTIR analysis,the bacterial cellulose produce appears to have very good crystallinity characteristics similar to the microcrystalline cellulose (MCC).SEM analysis concludes that the ribbon network is produce under the surface of bacterial cellulose.